Comparative clinical evaluation of the therapeutic effects of low-level laser and hyaluronic acid on gingivitis catarrhalis in children - Igić, Marija; Kesić, Ljiljana; Obradović, Radmila; Filipović, Gordana; Stojković, Branislava; Todorović, Kosta (Vojnosanitetski pregled, 2021)
Background/Aim. Gingivitis catarrhalis is the most common disease of the oral mucosa in children, representing an inflammation of the gingiva of an exudative nature. The aim of this study was to evaluate the effectiveness of low-level laser therapy and hyaluronic acid therapy on gingivitis catarrhalis in children using the appropriate clinical parameters. Methods. The study involved 100 children with permanent dentition in whom gingivitis catarrhalis had been diagnosed. The examinees were divided into two groups: the group I consisting of patients with gingival inflammation (50 examinees) in whom the therapy with hyaluronic acid was applied after the removal of soft and hard dental deposits, and the group II consisting of patients with gingival inflammation (50 examinees) in whom low-level laser therapy was applied after the removal of soft and hard dental deposits. Clinical evaluation of the therapeutic effects of low-level laser and hyaluronic acid on gingivitis catarrhalis was performed using the appropriate indices: the Greene-Vermillion Plaque Index (PI), Muhlemann bleeding index (BI), and Community Periodontal Index of Treatment Needs (CPITN). Results. Using the Student’s t-test for dependent samples, a statistically significant difference was obtained (p < 0.001) between the PI, BI, and CPITN indices before and after the therapy in both examined groups. Moreover, the CPITN index after the therapy in the group II was statistically significantly lower (p < 0.05) than that obtained in the group I. Conclusion. The results demonstrated an exceptional effect of hyaluronic acid and low-level laser therapy, supplementing basic therapy, in the treatment of catarrhal gingivitis in children. Somewhat better results were achieved with the combination of basic therapy and low-level laser.